Enhancement of nutritive value of palm kernel cake by solid state fermentation with Cellulomonas fimi - Hussin, N.; Abdullah, Norhani; Foo, Hooi Ling (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Palm kernel cake (PKC) is the solid residue left after the oil extraction of the palm kernel. It is used extensively in the animal feed industry especially as an ingredient for ruminant feed but has limited used in poultry feed due to its high fiber that can cause digestibility problems to the birds. Solid state fermentation (SSF) by microbial cultures has been proposed as a strategy for enhancing the nutritive value of feeds. Hence in this study, the cellulolytic bacterial species Cellulomonas fimi was evaluated for its potential to enhance the nutritive value of PKC by SSF. The SSF was conducted by inoculating ground and dried PKC with 1011colony forming unit of C. fimi per g PKC at a moisture ratio of 1:2.5. The fermentation lasted for 30 days. The results showed that SSF of PKC with C. fimi significantly (P<0.05) reduced the NDF, ADF, CF and ether extract. A significant (P<0.05) increase in reducing sugar and soluble protein was observed at day 30 of fermentation. The amount of reducing sugar increased to 9.968 mg/g at day 30 compared to untreated PKC which was 5.853 mg/g. The amount of soluble protein increased from 0.333 mg/g in untreated PKC to 3.295 mg/g in fermented PKC at day 30. Hence, C. fimi could be utilized to improve the nutritive value of PKC by SSF.